Divulging two decades of multimedia applications in biology education - Abdullah, Khairul Hafezad (Jurnal Inovasi Pendidikan IPA, 2023)
Biology is an indispensable component of Science, Technology, Engineering, and Mathematics (STEM) education. Accordingly, effective biology teaching necessitates multimedia to assist students in fathoming complex scientific themes. This study aims to scrutinise the bibliometrics of preceding publications on multimedia applications in biology education from the Scopus and Web of Science databases. This study explores descriptive publishing patterns and the emergence of academic discourse about multimedia applications in biology education using ScientoPy and VOSviewer. The results reveal publications on this topic have been volatile, with less than ten publications in both databases. The United States has bested others as the most noteworthy multimedia applications in biology education publication hubs. The top three keywords yielded by ScientoPy were "biology education", "visual literacy", and "science education". The keywords "active learning," "science education," "visual literacy," and "anatomy diagrams" generated by VOSviewer have been among the most employed keywords since 2016. In the abstract's content analysis, the keywords "visual representation" and "image" have often been utilised. This study provides an overview of the applications of multimedia in biology education. It will aid researchers interested in advancing or discovering new knowledge in this domain and developing splendid biology education research ideas and practices.